Expert consensus on the benefits of neuraminidase in conventional influenza vaccines: a Delphi study - John Youhanna; Joan Puig-Barberà; Matthew S. Miller; Deborah Molrine; Monica Hadi; Shweta Bapat; Ike Iheanacho; Sophie Dodman; Tsion Fikre; Paul Swinburn; ADD-NA (Adding Neuraminidase) Delphi panel (BMC Infectious Diseases)
Abstract Background Seasonal vaccination is the mainstay of human influenza prevention. Licensed influenza vaccines are regularly updated to account for viral mutations and antigenic drift and are standardised for their haemagglutinin content. However, vaccine effectiveness remains suboptimal. Neuraminidase (NA) evolves more gradually than hemagglutinin and has been demonstrated to provide added clinical benefits. However, NA is not currently a mandated or standardised component of influenza vaccines. Methods Here, we collated expert opinions on the importance of NA in influenza vaccines in a two-stage Delphi survey. Nine statements about NA were formulated by a steering committee based on a targeted literature review. In the survey’s first round, panellists recruited from three continents were requested to report on their agreement with each statement and estimate the strength of evidence for each statement. Panellists were also requested to explain their choice of answer and suggest revisions to the statements. Consensus was considered reached if ≥ 75% of panellists agreed with a statement. If consensus was not reached for a statement, this statement was revised and included in the survey’s second round. Results Nine panellists with a broad range of NA-related expertise, including clinical, research, and public health experience, completed the survey. They agreed that anti-NA responses acquired via natural infection or vaccination are associated with protective immunity independently of haemagglutinin and that NA provided additional advantages including improving disease severity metrics. The experts identified several knowledge gaps concerning heterologous cross-reactivity of vaccine-induced anti-NA antibodies, correlations between anti-NA titres and reduced transmission or infection risks, and differences in anti-NA responses to seasonal influenza vaccines. Conclusions NA is an important influenza vaccine component and is associated with specific benefits. These benefits would likely be greater if NA content were standardised. Additional research is needed to optimise vaccines for anti-NA effects.